Socioeconomic inequalities in hidden hunger, undernutrition, and overweight among under-five children in 35 sub-Saharan Africa countries - Michael Ekholuenetale; Godson Tudeme; Adeyinka Onikan; Charity E. Ekholuenetale (SpringerOpen, 2020)
Abstract Background Many underlying factors are assumed to contribute to the disparities in magnitude of childhood malnutrition. Notwithstanding, socioeconomic inequalities remain key measures to determine chronic and hidden hunger among under-five children. This study was undertaken to explore childhood malnutrition problems that are associated to household wealth-related and mother's educational attainment in sub-Saharan Africa (SSA). Methods Secondary data from birth histories in 35 SSA countries was used. The Demographic and Health Survey (DHS) data of 384,747 births between 2008 and 2017 in 35 countries was analyzed. The outcome variables of interest were mainly indicators of malnutrition: stunting, underweight, wasting, overweight, anemia, and under-five children survival. Household wealth-related and mother's educational level were the measures of socioeconomic status. Concentration index and Lorenz curves were the main tools used to determine inequalities for nutritional outcomes. The statistical significance level was determined at 5%. Results Based on the results, Burundi (54.6%) and Madagascar (48.4%) accounted for the highest prevalence of stunted children. Underweight children were 32.5% in Chad and 35.5% in Niger. Nigeria (16.6%) and Benin (16.4%) had the highest burdens of wasted children. Overall, overweight and under-five survival were significantly more in the higher household wealth, compared with the lower household wealth (Conc. Index = 0.0060; p < 0.001 and Conc. Index = 0.0041; p = 0.002 respectively). Conversely, stunting (Conc. Index = − 0.1032; p < 0.001), underweight (Conc. Index = − 0.1369; p < 0.001), wasting (Conc. Index = − 0.0711; p < 0.001), and anemia (Conc. Index = − 0.0402; p < 0.001) were significantly lower in the higher household wealth status, compared with the lower household wealth groups. Furthermore, under-five children survival was significantly more from mothers with higher educational attainment, compared with children from mothers with lower educational attainment (Conc. Index = 0.0064; p < 0.001). Conversely, stunting (Conc. Index = − 0.0990; p < 0.001), underweight (Conc. Index = − 0.1855; p < 0.001), wasting (Conc. Index = − 0.1657; p < 0.001), overweight (Conc. Index = − 0.0046; p < 0.001), and anemia (Conc. Index = 0.0560; p < 0.001) were significantly more among children from mothers with lower educational attainment. The test for differences between children from urban vs. rural was significant in stunted, underweight, overweight, and anemia for household wealth status. Also, the difference in prevalence between children from urban vs. rural was significant in stunted, underweight, and wasted for mother's educational attainment. Conclusion and recommendations Reduction in malnutrition could be achieved by socioeconomic improvement that is sustained and shared in equity and equality among the populace. Interventions which target improvement in food availability can also help to achieve reduction in hunger including communities where poverty is prevalent.